2009
DOI: 10.1007/s00340-009-3496-x
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-damage-assisted ferroelectric domain structuring in magnesium-doped lithium niobate

Abstract: Irradiation of 5% magnesium-doped lithium niobate crystals (LiNbO 3 :Mg) with high-energy, low-mass 3 He ions, which are transmitted through the crystal, changes the domain reversal properties of the material. This enables easier domain engineering compared to non-irradiated material and assists the formation of small-sized periodically poled domains in LiNbO 3 :Mg. Periodic domain structures exhibiting a width of ≈520 nm are obtained in radiation-damaged sections of the crystals. The ferroelectric poling beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…Note that the slope of this linear dependence was found to vary strongly with the specific sample and probe. Interestingly, although domain size has been commonly reported to depend on the pulse duration [4,5,20], our measurements, repeated over many experiments, showed that there was no such pulse-duration dependence. One tentative explanation is related to the limited mobility of space charge in the implantation layer, however more extensive studies must be done to understand this phenomenon.…”
contrasting
confidence: 52%
“…Note that the slope of this linear dependence was found to vary strongly with the specific sample and probe. Interestingly, although domain size has been commonly reported to depend on the pulse duration [4,5,20], our measurements, repeated over many experiments, showed that there was no such pulse-duration dependence. One tentative explanation is related to the limited mobility of space charge in the implantation layer, however more extensive studies must be done to understand this phenomenon.…”
contrasting
confidence: 52%
“…Because even Dn can be removed with annealing, 30 the additional conductivity as well as refractive index modifications do not hamper the usage of irradiated LiNbO 3 :Mg as source for PPLN. 20 From the limited thermal stability we can further conclude that defects in the electronic band structure are the reason for the conductivity. The temperature dependence of shows striking similarities to the stability of ion-induced changes in the coercive field E C 19 and color changes.…”
Section: A Conductivitymentioning
confidence: 93%
“…Besides this, ion exposure leads to a change in the coercive field E C 19 and to a better structuring capability of the ferroelectric domains of Mg-doped crystals. 20 Hence the treatment of LiNbO 3 with low-mass, high-energy ions is an interesting alternative to the common techniques mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…The renaissance of light-ferroelectric interactions has attracted significant research interest in recent years due to advancement in the understanding of underlying mechanisms. This has resulted in renewed interests in enhanced ferroelectric light energy conversion with large efficiency, and the development of new concepts such as domain wall photovoltaics, , tip-enhanced photovoltaic effects, and shift current models. Parallel ongoing investigations of the possibility of utilizing optical control of ferroelectric domains for the tuning of capacitance/resistive states, multiferroic states, and macroscopic polarization , have also opened new pathways for the creation of next-generation neuromorphic devices such as photodetectors, optical modulators, ferroelectric diodes, memristors, solaristors, optoelectric tunnel junctions, , and photoferroelectric generators. ,, Some commercial devices for optoelectronic applications of ferroelectrics are based on LiNbO 3 , with other materials being less explored. In this work, a cost-effective and easy-to-fabricate polycrystalline bulk ferroelectric (KNBNNO: ((K 0.5 Na 0.5 )­NbO 3 -2 mol % Ba­(Ni 0.5 Nb 0.5 )­O 3−δ )) ,, that has a 60% lower electro-optic poling energy requirement than LiNbO 3 crystals is presented.…”
Section: Introductionmentioning
confidence: 99%